2009
DOI: 10.1074/jbc.m804935200
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Trefoil Factor 2 Activates the CXCR4 Receptor in Epithelial and Lymphocytic Cancer Cell Lines

Abstract: The secreted trefoil factor family 2 (TFF2) protein contributes to the protection of the gastrointestinal mucosa from injury by strengthening and stabilizing mucin gels, stimulating epithelial restitution, and restraining the associated inflammation. Although trefoil factors have been shown to activate signaling pathways, no cell surface receptor has been directly linked to trefoil peptide signaling. Here we demonstrate the ability of TFF2 peptide to activate signaling via the CXCR4 chemokine receptor in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 74 publications
3
106
1
Order By: Relevance
“…All of the currently available results indicate TFFs, especially the endogenous gastric TFF2, accelerate gastric epithelial restitution (4). The downstream effectors of TFFs have been elusive, although it has recently been shown that TFF2 activates calcium-dependent signaling and ERK1/2 phosphorylation via the CXCR4 receptor, providing the first validation of a TFF receptor (5). As discussed in a recent review, the expanding information about signaling events stimulated by TFFs is broadening understanding of how restituting cells loosen contacts with neighboring cells, enhance their resistance to apoptosis, and initiate migration across a wound (3).…”
Section: -(N-ethyl-n-isopropyl) Amiloride or 25 M Hoe694) Slows Restimentioning
confidence: 99%
“…All of the currently available results indicate TFFs, especially the endogenous gastric TFF2, accelerate gastric epithelial restitution (4). The downstream effectors of TFFs have been elusive, although it has recently been shown that TFF2 activates calcium-dependent signaling and ERK1/2 phosphorylation via the CXCR4 receptor, providing the first validation of a TFF receptor (5). As discussed in a recent review, the expanding information about signaling events stimulated by TFFs is broadening understanding of how restituting cells loosen contacts with neighboring cells, enhance their resistance to apoptosis, and initiate migration across a wound (3).…”
Section: -(N-ethyl-n-isopropyl) Amiloride or 25 M Hoe694) Slows Restimentioning
confidence: 99%
“…However, all attempts have so far failed to convincingly demonstrate a typical transmembrane receptor for TFF2. Currently, TFF2 is considered a low affinity ligand for the chemokine receptor CXCR4 (40,41). Furthermore, integrin β1 as well as a large transmembrane glycoprotein with similarity to CRP-Ductin/ DMBT1/gp-340/hensin have been identified as TFF2 binding proteins in the porcine stomach (42).…”
Section: Tff2 a Muc6-binding Lectin Stabilizing The Gastric Mucus Bamentioning
confidence: 99%
“…CXCL12 also has an additional receptor, CXCR7, 45 which is believed to act as a decoy receptor to sequester the ligand; 46,47 however, CXCR7 does not appear to have a major role in hematopoiesis. 48 Additionally, there are several low-affinity ligands of CXCR4, such as trefoil factor 2 49 and defensin 50 but their significance in hematopoiesis is unclear. There is considerable evidence showing that CXCR4 signaling provides a key retention signal for HSPCs in the bone marrow.…”
Section: Cxcr4/cxcl12 Axismentioning
confidence: 99%